Indonesia Komunikasi Persuasif dalam Menyampaikan Pesan Moral pada Anak Usia Sekolah - Nazdah Issyatu Rachman; Rahayu Anniza Ayu (Jurnalika : Jurnal Ilmu Komunikasi, 2026)
Moral development in school-aged children is strongly influenced by the quality of communication within family and school environments. Persuasive communication is regarded as an effective approach in moral education as it emphasizes emotional engagement, dialogical interaction, and voluntary acceptance of values. This study aims to analyze the role of persuasive communication in delivering moral messages to school-aged children.This research employs a qualitative approach using a literature review method. Data were collected from scientific journals and relevant academic sources related to persuasivecommunication and moral education. The analysis was conducted through descriptive qualitative techniques by synthesizing key findings from previous studies.The findings indicate that persuasive communication supports the internalization of moral values when applied through empathetic interaction, role modeling, and consistent message delivery by parents and teachers. This study concludes that persuasive communication is a strategic approach to strengthening moral education for school-aged children.